1988
DOI: 10.1007/bf01535735
|View full text |Cite
|
Sign up to set email alerts
|

Gastric motility is an important factor in the pathogenesis of indomethacin-induced gastric mucosal lesions in rats

Abstract: Effects of atropine, cimetidine, and 16,16-dimethyl prostaglandin E2 (16,16-dmPGE2) on indomethacin-induced gastric lesions were investigated in rats by correlating their effects on gastric acid and HCO3- secretion and motility. Subcutaneously administered indomethacin (25 mg/kg) produced gastric mucosal lesions within 4 hr. In parallel studies, an equivalent dose of indomethacin inhibited gastric HCO3- secretion, and stimulated gastric motor activity measured as intraluminal pressure recordings, whereas acid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
2

Year Published

1992
1992
2003
2003

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 24 publications
3
53
0
2
Order By: Relevance
“…Takeuchi et al (8,9) reported increased amplitude of antral contractions in indomethacin-induced gastric lesions in rats and suggested that gastric hypercontractility could play an important role in the pathogenesis of this condition. However, Fioramonti and Bueno (10) showed that indomethacin-induced gastric ulceration was associated with (11) were not able to show any difference in gastric antral motility after NSAID administration in men.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Takeuchi et al (8,9) reported increased amplitude of antral contractions in indomethacin-induced gastric lesions in rats and suggested that gastric hypercontractility could play an important role in the pathogenesis of this condition. However, Fioramonti and Bueno (10) showed that indomethacin-induced gastric ulceration was associated with (11) were not able to show any difference in gastric antral motility after NSAID administration in men.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that NSAIDs are associated with altered gastroduodenal motility (6)(7)(8)(9)(10). Some data indicate that the administration of NSAIDs is followed by either increased gastric contractility, which correlates with gastric damage (6-9) or decreased intestinal spiking amplitude and disruption of migrating motor complexes (10), with no correlation with gastric damage.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The length (mm) of each lesion was measured, summed per stomach and used as a lesion score. In a separate study, the stomachs were perfused with 150 mM HCl (1 ml/hr) during a 4-hr test period according to the previously published method (12). Acid perfusion was started im mediately after injection of indomethacin, the animals were killed 4 hr later, and the stom achs were treated with formalin and examined for lesions.…”
Section: Macroscopic Evaluation Of Gastric Lesionsmentioning
confidence: 99%
“…However, withdrawal from such therapy is not always practicable in patients who need analgesics and antipyretics (1). The basis of NSAIDs-induced gastric damage is thought to be multifactorial (2,3): i) suppression of mucosal prostaglandin (PG) synthesis via inhibition of cyclooxygenase, ii) decrease in the transmucosal potential difference, iii) decrease in mucosal blood flow, iv) effects on neutrophil function, v) inhibition of gastric HC03-secretion, and vi) enhancement of gastric motility. Among these, inhibition of PG synthesis probably plays a key role because PGs, particularly PGE2 and PGI2, are known to function in gastric defense by inhibiting acid secretion and by increasing mucus secretion and blood flow (4).…”
mentioning
confidence: 99%